2018
DOI: 10.2478/johh-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Modis Snowline Elevation Changes During Snowmelt Runoff Events in Europe

Abstract: This study evaluates MODIS snow cover characteristics for large number of snowmelt runoff events in 145 catchments from 9 countries in Europe. The analysis is based on open discharge daily time series from the Global Runoff Data Center database and daily MODIS snow cover data. Runoff events are identified by a base flow separation approach. The MODIS snow cover characteristics are derived from Terra 500 m observations (MOD10A1 dataset, V005) in the period 2000-2015 and include snow cover area, cloud coverage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Comparisons of MODIS-derived snowlines from high-resolution DEMs and field-based studies have shown good agreement [5,38]. Additionally, the RSLE method by [14] has been widely used to investigate snow dynamics [37,[39][40][41][42]. This method estimates the elevation at which the number of snow-free pixels above the elevation line and the number of snowy pixels below the elevation line are at their minimum above and below the elevation line.…”
Section: Snowline Altitude Estimationmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparisons of MODIS-derived snowlines from high-resolution DEMs and field-based studies have shown good agreement [5,38]. Additionally, the RSLE method by [14] has been widely used to investigate snow dynamics [37,[39][40][41][42]. This method estimates the elevation at which the number of snow-free pixels above the elevation line and the number of snowy pixels below the elevation line are at their minimum above and below the elevation line.…”
Section: Snowline Altitude Estimationmentioning
confidence: 95%
“…The snowline altitude was derived from the MODIS snow product and elevation data using the regional snowline elevation (RSLE) method developed by [14]. The snowline has been widely derived using the MODIS snow product in different parts of the world [35][36][37]. Comparisons of MODIS-derived snowlines from high-resolution DEMs and field-based studies have shown good agreement [5,38].…”
Section: Snowline Altitude Estimationmentioning
confidence: 99%
“…To date, different EO techniques (e.g., optical, radar, passive microwave, altimetry) have provided a timely, promising, and efficient approach to retrieve snow dynamics, including snowmelt processes [10]. Previous studies characterized snowmelt processes with several spatial parameters: SCA [11,12], snow line elevation (SLE) [13][14][15], or with temporal parameters: snowmelt onset (SMO) [3,16], snow cover duration (SCD) [17,18], and snow persistence (SP) [19,20]. Besides, to further capture the spatiotemporal dynamics of SCA throughout an ablation season, snow depletion curves (SDCs) are often utilized [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Space-born remote sensing data have the potential to provide estimates of certain snow properties [25]. In the visible (VIS) and near infrared (NIR) spectral range space-borne remote sensors (e.g., MODIS, AVHRR, Sentinel-2) can determine the snow cover extent (SCE) and snow cover fraction (SCF) at a high spatial resolution and long time-series of these data exist (e.g., [26][27][28][29][30][31][32][33]). The observation of snow cover area is of particular value in headwaters of mountainous regions [34][35][36] and one can expect to obtain volume information thanks to recent advances in photogrammetry and in the availability of stereo image [37].…”
Section: Introductionmentioning
confidence: 99%